Mechanism of adhesion failure during interrupted cutting with cemented carbide tools: Experimental and ab-initio perspective. (August 2021) - Gao, Siyuan; Zheng, Minli; Zhu, Jiachen; Chen, Jinguo
Abstract: Considering the frequent occurrence of adhesion failure of the cemented carbide tool during interrupted cutting of heavy parts, resulting in the sudden failure of the tool when it is far from reaching its design life. The mechanisms of adhesion failure were investigated. Adhesion failure tests were performed with an interrupted cutting operation. The microstructure of the tool-chip adhesion interface and its adjacent region were characterized using scanning electron microscopy and spherical aberration-corrected transmission electron microscopy. The phase boundaries (PBs) strength of WC/Co interfaces strength in cemented carbide tool after cutting tests were evaluated by ab-initio calculations. The results indicate that at the WC/Co interfaces of the tool-chip interface adjacent region, Co binder phase with the hcp crystal structure is detected and is accompanied by the segregation of impurities, such as Fe and Cr. Based on results from high-resolution transmission electron microscopy, approximation models of the WC/Coα and WC/Coβ interfaces were constructed. The interface strength and stability for WC/Coβ are considerably lower than those of WC/Coα, and the segregated deposition of Fe in the two types of termination PBs will reduce the strength and stability of the interface. Finally, the mechanism of the tool adhesion failure is found to arise from the significantly reduced interfacial strength of the cemented carbide material in the vicinity of the tool-chips under the action of the interrupted cutting load. As the number of mechanical-thermal shock cycles increases, the cracks follow the weakened PB large-scale expansion, and large pieces of tool material leave the rake face with the movement of the chip. Graphical abstract: Unlabelled Image Highlights: Tool-chip adhesion interface were characterized on multi-scale. At the WC/Co phase-boundaries of the tool-chip interface, Co binder-phase with hcp structure is detected and is accompanied by the segregation of impurities. Approximation models of the WC/Coα and the WC/Coβ PBs were constructed based on HRTEM characterization. The effects of impurities and martensitic transformation of Co were estimated by DFT calculation.